Different Proteome Profiles between Male and Female Populus cathayana Exposed to UV-B Radiation - Zhang, Yunxiang; Feng, Lihua; Jiang, Hao; Zhang, Yuanbin; Zhang, Sheng (Frontiers in Plant Science, 2017)
With increasing altitude, solar UV-B radiation is enhanced. Based on the phenomenon of male-biased sex ratio of Populus cathayana Rehder in high altitude alpine area, we hypothesized that males have a faster and more sophisticated responsive mechanism to high UV-B radiation than that of females. Our previous studies have shown sexually different responses to high UV-B radiation were existed in P. cathayana at the morphological, physiological and transcriptomic levels. However, the responses at the proteomic level remain unclear. In this study, an isobaric tag for relative and absolute quantification (iTRAQ)-based quantitative proteome analysis was performed in P. cathayana females and males. A total of 2405 proteins were identified, with 331 proteins defined as differentially expressed proteins (DEPs). Among of these, 79 and 138 DEPs were decreased and 47 and 107 DEPs were increased under high solar UV-B radiation in females and males, respectively. A bioinformatics analysis categorized the common responsive proteins in the sexes as related to carbohydrate and energy metabolism, translation/transcription/post-transcriptional modification, photosynthesis and redox reactions. The responsive proteins that showed differences in sex were mainly those involved in amino acid metabolism, stress response and translation/transcription/post-transcriptional modification. This study provides proteomic profiles that poplars responding to solar UV-B radiation, and it also provides new insights into differentially sex-related responses to UV-B radiation.